Overlapping Water and Nutrient Use Efficiencies and Carbon Assimilation between Coexisting Simple- and Compound-Leaved Trees from a Valley Savanna - Wang, Yang-Si-Ding; Yang, Da; Wu, Huai-Dong; Zhang, Yun-Bing; Zhang, Shu-Bin; Zhang, Yong-Jiang; Zhang, Jiao-Lin (Water (Basel), 2020)
Identifying differences in ecophysiology between simple and compound leaves can help understand the adaptive significance of the compound leaf form and its response to climate change. However, we still know surprisingly little about differences in water and nutrient use, and photosynthetic capacity between co-occurring compound-leaved and simple-leaved tree species, especially in savanna ecosystems with dry-hot climate conditions. From July to September in 2015, we investigated 16 functional traits associated with water use, nutrients, and photosynthesis of six deciduous tree species (three simple-leaved and three compound-leaved species) coexisting in a valley-savanna in Southwest China. Our major objective was to test the variation in these functional traits between these two leaf forms. Overall, overlapping leaf mass per area (LMA), photosynthesis, as well as leaf nitrogen and phosphorus concentrations were found between these coexisting valley-savanna simple- and compound-leaved tree species. We didn’t find significant differences in water and photosynthetic nitrogen or phosphorus use efficiency between simple and compound leaves. Across these simple- and compound-leaved tree species, photosynthetic phosphorus use efficiencies were positively related to LMA and negatively correlated with phosphorus concentration per mass or area. Water use efficiency (intrinsic water use efficiency or stable carbon isotopic composition) was independent of all leaf traits. Similar ecophysiology strategies among these coexisting valley-savanna simple- and compound-leaved species suggested a convergence in ecological adaptation to the hot and dry environment. The overlap in traits related to water use, carbon assimilation, and stress tolerance (e.g., LMA) also suggests a similar response of these two leaf forms to a hotter and drier future due to the climate change.